The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.cgd.2c00382
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bonded Cocrystals of 1,3,5-Triiodo-2,4,6-trifluorobenzene and Structural Isomers of Benzoylpyridine

Abstract: Six novel halogen-bonded cocrystals of 1,3,5-triiodo-2,4,6-trifluorobenzene with three structural isomers of benzoylpyridine have been synthesized mechanochemically and by crystallization from solution, five of which were structurally characterized. In four cocrystals, benzoylpyridine is a ditopic halogen-bond acceptor participating in halogen bonding with both pyridine nitrogen and carbonyl oxygen atoms, while in one cocrystal, only the I···N halogen bond has formed. In general, the I···N halogen bonds are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…EGDMA-polymer showed higher affinity than DVB-polymer for these iodinated compounds (Figure S4). The higher affinity on EDGMA-polymer was probably attributable to the lone pair of carbonyl oxygen atoms, a potential halogen bonding acceptor. , In fact, carbonyl oxygen atoms and ether oxygen atoms could act as a reliable halogen-bonding acceptors in the presence of a nitrogen atom . The affinity for DVB-polymer was contrarily negligible, although our previous report suggested that aromatic rings could also act as a halogen bond acceptors .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…EGDMA-polymer showed higher affinity than DVB-polymer for these iodinated compounds (Figure S4). The higher affinity on EDGMA-polymer was probably attributable to the lone pair of carbonyl oxygen atoms, a potential halogen bonding acceptor. , In fact, carbonyl oxygen atoms and ether oxygen atoms could act as a reliable halogen-bonding acceptors in the presence of a nitrogen atom . The affinity for DVB-polymer was contrarily negligible, although our previous report suggested that aromatic rings could also act as a halogen bond acceptors .…”
Section: Resultsmentioning
confidence: 86%
“…41,56 In fact, carbonyl oxygen atoms and ether oxygen atoms could act as a reliable halogen-bonding acceptors in the presence of a nitrogen atom. 57 The affinity for DVB-polymer was contrarily negligible, although our previous report suggested that aromatic rings could also act as a halogen bond acceptors. 51 As a result, DVB was utilized as the crosslinker to synthesize MIPs.…”
Section: ■ Introductionmentioning
confidence: 93%
“…10 Moreover, intra- and intermolecular XB involving aromatic N am and N py are gaining increasing attention for their employment in supramolecular design, crystal engineering, catalyst development, halogen related enzymatic mechanisms and pharmaceutical synthesis. 11–21…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic nitrogen atoms are the most studied and reliable acceptor species, and this is especially the case for pyridine nitrogen atoms, 26 to the point that they are a valuable benchmark for donor evaluation 9,27,28 and studies on acceptor competitiveness. 29,30 In recent years, they have been followed by a variety of other, mostly nitrogen or oxygen atom containing species, such as methoxy, 31−33 nitro, 34−37 hydroxyl, 32,33,38 and nitrile 32,39−41 functional groups, and oxygen atoms in Noxides. 42,43 Some recent studies also showcased the promising halogen bond acceptor potential of nitrogen atoms in piperazine 10 and nitrogen and oxygen atoms in morpholine 10,44 as well as the carbonyl oxygen atom.…”
mentioning
confidence: 99%
“…In the last three decades, the halogen bond , has become recognized as a valuable tool in crystal engineering. Because of its larger directionality (as compared to the hydrogen bond) , and tunability achievable by changing the donor halogen atom in otherwise structurally equivalent donor molecules, the halogen bond found its way into a rising number of scientific studies on the synthesis and design of functional materials as well as organic synthesis, , solution chemistry, , pharmaceutical, and theoretical chemistry. , The list of studied halogen bond donors and especially halogen bond acceptors grows continuously. Cyclic nitrogen atoms are the most studied and reliable acceptor species, and this is especially the case for pyridine nitrogen atoms, to the point that they are a valuable benchmark for donor evaluation ,, and studies on acceptor competitiveness. , In recent years, they have been followed by a variety of other, mostly nitrogen or oxygen atom containing species, such as methoxy, nitro, hydroxyl, ,, and nitrile , functional groups, and oxygen atoms in N -oxides. , Some recent studies also showcased the promising halogen bond acceptor potential of nitrogen atoms in piperazine and nitrogen and oxygen atoms in morpholine , as well as the carbonyl oxygen atom. , So far, systematic studies of halogen bonding with these moieties were mainly limited to smaller building blocks. Searching the Cambridge Structural Database, one can find a small number of larger, relatively bulky building blocks that are halogen bonded via either the ...…”
mentioning
confidence: 99%